Applying RUSLE for soil erosion estimation in Romania under current and future climate scenarios - Patriche, Cristian Valeriu (Geoderma Regional, 2023)
Soil erosion is one of the main land degradation processes, often enhanced by unsuitable human activities. In the context of global climate change, soil erosion also exhibits quantitative and qualitative changes induced by the temporally dynamic erosion factors, namely rainfall erosivity and land use. Our study attempts to forecast the evolution of soil erosion rates under climate change scenarios over the Romanian territory. Firstly, we apply the Revised Universal Soil Loss Equation (RUSLE) methodology to achieve a spatial model of soil erosion for the current climate conditions. Secondly, we use projections of rainfall erosivity to derive soil erosion models for two future climate change scenarios (Representative Concentration Pathway - RCP 4.5 and 8.5) and two periods of time (2041–2060, 2061–2080). Thirdly, we compute the differences between future projected and current erosion rates to identify spatial patterns of soil erosion evolution. The results show that, under the influence of rainfall erosivity dynamics, soil erosion tends to increase during the next decades. Overall, an enhancement of soil erosion rates on 84–90% of the country is expected to take place. Most of the erosion rates will increase slightly, with <1 t ha−1 yr−1, from an overall average of 2.94 t ha−1 yr−1, at present, to 3.67 (2061–2080, RCP 8.5) – 3.74 (2041–2060, RCP 8.5) t ha−1 yr−1 at country level. Locally, the erosion rates may increase with >5–10 t ha−1 yr−1 on areas estimated to cumulate >8000 km2. The most affected areas will be the soils situated in hilly and plateau regions, leading to an enhancement of their fertility degradation. •RUSLE model is used to achieve high resolution (25 × 25 m) maps of current and future soil erosion in Romania•Current soil erosion estimates are validated with measured erosion rates•Erosion models are prepared for RCP 4.5 and 8.5 climate change scenarios in Romania for the first time•Erosion rates are likely to increase in the future on most of the Romanian territory•The most affected areas will be the soils situated in hilly and plateau regions